Single‐ended electrical impedance tomography. Issue 4 (12th April 2018) - Salama, Abdalla; Malekmohammadi, Amin; Mohanna, Shahram
Abstract : A novel prototype electrical impedance tomography (EIT) system, which uses single‐ended signalling, is presented. The single‐ended electrical impedance tomography system consists of a host computer, data acquisition system, switching box, MATLAB, and LabVIEW program. Ability of the system to detect and track hidden conductive and non‐conductive objects was examined using a beaker (cylindrical shape) of 180 mm diameter and 280 mm height, filled with 3000 mL tap water, and with 16 electrodes attached. Stainless steel and Teflon rods with different sizes were placed in different locations inside the beaker, and images were obtained. All the objects were tested under multiple signal injection frequencies in the range of 12–1000 kHz. The results showed that the system could detect and track conductive and non‐conductive objects during certain injection frequencies. The single‐ended EIT system requires one wire connection to make one signal injection or measurement, and this is controlled using a multiplexer or switching box. Alternatively, an ordinary EIT system requires additional wire connections for single data measurement or injection, and a more complex circuit to control the I/O signals. This greater number of wires and increased circuit complexity will increase the data error rate and the cost significantly.